2018
DOI: 10.1007/s11523-018-0602-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Predictive and Prognostic Values of Stromal Tumor-Infiltrating Lymphocytes in HER2-Positive Breast Cancers treated with neoadjuvant chemotherapy

Abstract: BackgroundStromal tumor-infiltrating lymphocytes (sTILs) have been identified as a predictive biomarker for response to neoadjuvant chemotherapy (NAC) and prognosis in human epidermal growth factor receptor 2 (HER2)-positive breast cancers. However, standardized scoring methods for use in clinical practice need to be established, and the optimal threshold of sTILs to predict pathological complete response (pCR) and prognosis in HER2+ breast cancers has not yet been defined.ObjectiveThe predictive and prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…We analyzed the relationship between TILs and clinicopathological characteristics. As reported in most literature, total TILs are not associated with age or tumor size in breast cancer patients [33,35,39,43,50]. Earlier published showed that there was major correlation between the expression of TILs and lymph node status [49,52], which was similar with our research.…”
Section: Correlation Of Tils With Clinicopathological Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…We analyzed the relationship between TILs and clinicopathological characteristics. As reported in most literature, total TILs are not associated with age or tumor size in breast cancer patients [33,35,39,43,50]. Earlier published showed that there was major correlation between the expression of TILs and lymph node status [49,52], which was similar with our research.…”
Section: Correlation Of Tils With Clinicopathological Parameterssupporting
confidence: 91%
“…1). Finally, 11 potentially eligible RCTs [33][34][35][36][37][38][39][40][41][42]54] and 11 case-control studies [43][44][45][46][47][48][49][50][51][52][53] were considered, consisting of approximately 8 052 participants. The population of patients in each study varied from 50 to 1 060 cases, and the follow-up time ranged from 3.4 to 120 months.…”
Section: Search Results and Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…98 Both of them were associated with pCR in HER2+ and TNBC breast cancers. 95,99,100 The Breast International Group 02-08 trial indicated that each 10% elevation in intra-tumoral and stromal TILs was respectively related to 17% and 15% reduced relapse risk (adjusted P=0.1 and P=0.025), 27% and 17% reduced death risk (adjusted P=0.035 and P=0.023) in node-positive, ER-/HER2-breast cancer patients. 101 Interestingly, sTILs alone may be an essential evaluation in the assessment of pCR rates to NAC and prognosis in HER2+ breast cancers.…”
Section: Tumor-infiltrating Lymphocytes (Tils)mentioning
confidence: 99%
“…101 Interestingly, sTILs alone may be an essential evaluation in the assessment of pCR rates to NAC and prognosis in HER2+ breast cancers. 100,102 The majority of TILs are T lymphocytes, and B lymphocyte infiltrations are less common. 103 Abundant counts of CD8+ TILs were verified to be associated with improved prognosis and prolonged survivals of less aggressive breast cancer subtypes with over 1300 cases.…”
Section: Tumor-infiltrating Lymphocytes (Tils)mentioning
confidence: 99%
“…Fifteen of these researches provided HRs data of DFS or OS and we performed the pooled analysis. Twelve researches furnished HRs data of DFS [5, 13, 15-17, 24, 26, 29-31, 37, 40], and ten researches furnished HRs data of OS [5,13,15,17,18,20,21,24,26,29]. Table 1, summarized the main baseline characteristics.…”
Section: Baseline Characteristics Of Quali Ed Researchesmentioning
confidence: 99%